Theological Reflections on Gender Justice: How Indonesian Theology Confronts Gender Inequality and Violence (Indonesian Theological Justice Review, 2025)
Gender inequality and violence remain significant challenges in Indonesia, affecting women and marginalized gender groups across various socio-economic strata. This paper explores how Indonesian theological traditions—Islamic, Christian, and others—address gender justice, with a particular focus on gender-based violence (GBV) and women’s empowerment. The study analyzes key theological texts and teachings, exploring how religious leaders and institutions frame the issue of gender justice. In Islamic theology, the principles of qawwamun (responsibility) and adl (justice) are examined in relation to women's roles and rights, while Christian theology’s emphasis on the inherent dignity of all individuals is explored as a basis for advocating gender equality. Additionally, indigenous beliefs and practices regarding gender roles and balance within communities are also explored. The paper examines how these theological frameworks inform grassroots movements, gender advocacy, and religious-based initiatives for women’s rights in Indonesia. It concludes by assessing the theological responses to the growing issue of GBV and proposes the integration of gender justice into religious education and social advocacy programs as a means of empowering women and combating patriarchal systems.